2017
DOI: 10.1007/s10577-017-9566-8
|View full text |Cite
|
Sign up to set email alerts
|

Do holocentric chromosomes represent an evolutionary advantage? A study of paired analyses of diversification rates of lineages with holocentric chromosomes and their monocentric closest relatives

Abstract: Despite most of the cytogenetic research is focused on monocentric chromosomes, chromosomes with kinetochoric activity localized in a single centromere, several studies have been centered on holocentric chromosomes which have diffuse kinetochoric activity along the chromosomes. The eukaryotic organisms that present this type of chromosomes have been relatively understudied despite they constitute rather diversified species lineages. On the one hand, holocentric chromosomes may present intrinsic benefits (chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…The availability of genomics data could therefore allow to dissect at a genome-level the origin of holocentrism in order to better understand if the same genes (or different) have been coopted to favour the shift from mono-to holocentrism. Lastly, a more detailed study of the holocentric chromosomes evolution could be useful to understand which costs and advantages acted as main drivers in the evolution of the chromosome structure in order to better understand the multiple shifts from mono-to holocentrism (and vice versa) that occurred during both plant and animal evolution, even within recent lineages [63].…”
Section: Future Directionsmentioning
confidence: 99%
“…The availability of genomics data could therefore allow to dissect at a genome-level the origin of holocentrism in order to better understand if the same genes (or different) have been coopted to favour the shift from mono-to holocentrism. Lastly, a more detailed study of the holocentric chromosomes evolution could be useful to understand which costs and advantages acted as main drivers in the evolution of the chromosome structure in order to better understand the multiple shifts from mono-to holocentrism (and vice versa) that occurred during both plant and animal evolution, even within recent lineages [63].…”
Section: Future Directionsmentioning
confidence: 99%
“…The studies on artificial chromosomal rearrangements in various holocentric species showed that chromosome fragments retaining centromere activity are transmitted during mitosis and meiosis (Jankowska et al 2015 ). Comparisons of diversification rates between monocentric and holocentric sister clades in animals and plants did not detect an increase in diversification in holocentric species (Marquez-Corro et al 2018 ). Nevertheless, these analyses depend on the correct identification of the centromere type in a large number of lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, centromeric proteins and the kinetochore complex can change also in response to fluctuations in kinetochore protein levels (reviewed in [122]). Some organisms, such as Caenorhabditis elegans, have diffuse centromeres (holocentromeres) of unclear evolutionary advantage [123]. Despite the differences in DNA sequences, proteins composition and centromere size, all of these diverse centromere structures promote efficient chromosome segregation, balancing genome stability and adaptability, and ensuring faithful genome inheritance at each cellular generation.…”
Section: Centromere Flexibility In Response To Stressmentioning
confidence: 99%